Implementation of the Spread Spectrum Steganography Method for Embedding Secret Messages in Digital Image Media - Jonatan Carlos Rajagukguk; Yefta Roma Zebua; Wita Manik (BIOS: Jurnal Informatika dan Sains, 2026)
The development of information technology has increased the need for data security in the process of digital information exchange. In addition to cryptography, steganography has become an effective approach to maintaining data confidentiality by hiding messages within digital media without raising suspicion. One steganographic method with a high level of security is the Spread Spectrum method. This method works by spreading the message signal across a wide frequency spectrum so that it resembles noise and is difficult to detect. This study aims to examine and implement the Spread Spectrum steganography method in digital image media as a means of embedding secret messages. The method used includes the process of spreading the message using a pseudo-random code, embedding it into the image, and extracting the message on the receiver side. The results of the study indicate that the Spread Spectrum method is capable of hiding messages with a high level of imperceptibility and good robustness against disturbances. Therefore, this method is suitable for application in digital information security systems